Writing Difficulties of Accounting Students: A Cognitive, Linguistic, and Affective Analysis - Patty, Jusak; Lekatompessy, Felicia Miranda (Prodi Pendidikan Bahasa Inggris, Program Studi Diluar Kampus Utama (PSDKU) Unpatti-MBD, 2025)
This study examines the writing difficulties faced by second-semester accounting students through the cognitive-linguistic-affective framework. Despite the growing importance of written communication in accounting professions, research on discipline-specific writing challenges remains limited, particularly regarding how cognitive, linguistic, and affective factors manifest in specialized contexts. This descriptive quantitative study employed survey methodology with 52 second-semester accounting students at Pattimura University in Indonesia. A structured questionnaire measured writing difficulties across three dimensions using a 5-point Likert scale. Results revealed that linguistic challenges (M=3.18) were the most significant, followed by affective (M=3.06) and cognitive dimensions (M=3.04). Writing anxiety about consequential errors (M=3.54) and vocabulary limitations (M=3.21) emerged as the highest-scoring subdimensions, suggesting a cyclical relationship between language deficiencies and emotional responses. Audience-appropriate terminology adaptation (M=3.29) and integrating numerical data within coherent textual structures (M=3.23) presented distinctive challenges specific to accounting discourse. Demographic analysis showed minimal gender differences but identified higher linguistic difficulties among students with basic English proficiency. These findings underscore the need for integrated pedagogical approaches that address technical competencies, linguistic development, and psychological barriers in accounting education. The study extends the current understanding of writing difficulties beyond general academic contexts into specialized professional areas, providing evidence-based insights for designing targeted writing instruction in accounting programs.